The Assessment of The Quality of Financial Statements After the Conversion to IFRS Using Non-Earning Management Measures: The Case of Poland - Agnieszka PIECHOCKA-KALUZNA (Communications of International Proceedings, 2021)
The globalization of the economy has forced the harmonization of regulations, also those pertaining to accounting and financial reporting. This resulted in the adoption of International Accounting Standards (IAS) and International Financial Reporting Standards (IFRS) by an increasing number of countries. This paper is a description of the author’s several years of research, completed in 2020, on quality changes in financial reporting in Poland resulting from the implementation of IAS/IFRS. The research was conducted on the entire population of companies listed on the Warsaw Stock Exchange (WSE) in the years 2005-2019 which shifted from Polish regulations to IAS/IFRS. To achieve comparability with other similar studies of this type carried out worldwide, the author has conducted research in earning management (already described) and research in timely loss recognition and value relevance (described in this paper for the first time) on the abovementioned research group. However, the methods used before have been supplemented by the inclusion of some relevant information, the most important of which, as the author believes, was the use of the XGBoost method. The results obtained indicate that, even though due to the implementation of IAS/IFRS financial statements are characterized by higher quality, the difference in quality is very inconsiderable which means that the quality of Polish regulations was satisfactory.
Keywords: Accounting harmonization; accounting adoption; accounting quality; financial statements; IFRS.